The Friendship Route : The largest sculptural exhibition of the world art - Gallegos Navarrete, Blanca Margarita (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The Friendship Route emerged on the occasion of the XIX Olympiad in Mexico. Being the longest sculptural corridor in the world, where along sixteen kilometers were located 19 monumental sculptures of abstract art, it marked the starting point of a new public art, away from nationalisms. For this route to become a reality it involved hard work, from its management to its construction that is usually not mentioned when talking about it. More than fifty years after its creation, it is still a sample of the best of the world art of the sixties.